Interrelationships among jumping power, sprinting power and pubertal status after controlling for size in young male soccer players - Cunha, G. S.; Cumming, S. P.; Valente-dos-Santos, J.; Duarte, J. P.; Silva, G.; Dourado, A. C.; Leites, G. T.; Gaya, A. C.; Reischak-Oliveira, A.; Coelho e Silva, M. (Perceptual and Motor Skills, 2017)
This study examined power output on jumping and sprinting tests in young soccer players of differing pubertal status, while controlling for body size with allometric scaling exponents. A total of 46 males aged 12-18 years (14.17 years) were divided into three groups: pre-pubescent (n=12), pubescent (n=22), and post-pubescent (n=12). Participants performed a series of tests, including the squat jump (SJ), countermovement jump (CMJ), and 10-meter and 30-meter sprint test protocols. The Post-PUB group was older (F=112.411, p<0.001), more experienced in competitive soccer (F=8.055, p=0.001), taller (F=28.940, p<0.001), and heavier (F=20.618, p<0.001), when compared to peers in the other groups. Mean differences in jumping and sprinting performances suggested a significant effect for pubertal status on performance in the 10-meter sprint (large effect size, F=8.191, p<0.001) and 30-meter sprint (large effect size, F=8.093, p<0.001) after allometric scaling. Power output derived from SJ (small effect size, F=0.536, p=0.001) and CMJ (small effect size, F=1.058, p=0.356) showed no significant differences across players of varying pubertal status. Biological maturation showed a large effect on maximal power output for sprints, but not for jumps, when the effect of body size was adjusted by statistically derived allometric exponents in young male soccer players.